Data analytics as a necessary component of professional and civic competencies - Topalova, Svitlana; Torianyk , Zhanna (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
In today’s world, government institutions and organizations generate and publish vast amounts of data. These data have become the foundation for transparent governance and a source of ideas and innovations for businesses. Therefore, the ability to analyze big data and open data has become an essential component of both general and professional competencies across various fields. European and American universities have already begun to actively implement educational programs that include data analytics components. Researching and adapting their experiences is necessary to quickly bridge the significant gap between Ukrainian universities and global standards. Research Goal. The aim of the study is to determine the relevance of developing data analytics competencies among higher education students, as well as to analyze the experiences of European and American universities in implementing related educational programs and components. The primary object of the study is the educational programs of European and American universities. Materials And Methods. The methodology includes: comparative analysis of the content of scientific publications, documents from European institutions, and university educational programs; generalization and systematization of research results and analysis of educational program content. Results. It has been found that data analytics competencies are among the most important and strategic skills for modern professionals. The study shows that European and American universities are actively implementing new educational programs to train specialists in data analytics and are incorporating relevant courses into their programs across various sectors, including management. The main components of educational programs that ensure the development of data analytics competencies among students have been identified. Practical value. Recommendations have been formulated for improving educational programs by including relevant competencies and courses in data analytics. Conclusions. The key findings can be used to supplement the list of general and professional competencies, to develop new educational and professional programs, and to improve existing programs, particularly for the "Management" specialty.